Early Intervention for Mental Health Problems in Children: A New Therapeutic Technique - Nur, Rezeki; Rahmi, Sri Nur; Zou, Guijiao (Research Psychologie, Orientation et Conseil, 2024)
Mental health problems in children have been increasing at an alarming rate, leading to long-term consequences for both individuals and society. Early intervention is critical to prevent the development of severe mental health disorders in later life. Traditional methods of treatment often focus on managing symptoms, but emerging therapeutic techniques have shown promise in addressing underlying issues more effectively. This study aims to explore the effectiveness of a new therapeutic technique designed for early intervention in children with mental health problems. The goal is to evaluate how this approach can improve emotional regulation, reduce symptoms, and foster long-term mental well-being. A cohort of 100 children, aged 6 to 12 years old, who exhibited early signs of anxiety, depression, or behavioral disorders, participated in a 12-week intervention program. The new therapeutic technique, which combines cognitive-behavioral strategies with mindfulness practices, was applied in weekly sessions. Data were collected through pre- and post-intervention assessments using standardized mental health scales and parent-reported measures. The results indicated a significant reduction in anxiety and depressive symptoms among the children who participated in the program. Additionally, improvements were observed in emotional regulation and overall behavioral functioning, with over 75% of participants showing clinically meaningful changes. Parents also reported enhanced social interactions and a decrease in problematic behaviors. The new therapeutic technique for early intervention in children with mental health problems shows promising results. This approach not only alleviates symptoms but also supports emotional and behavioral development, contributing to long-term mental health improvements.